The impact of public spending on roads infrastructure on Malawi's economic growth - Makhwatha, Alex Simeon (Research of GSB, 2018)
Public expenditure has been a cardinal objective of all successive governments since Malawi gained its independence in 1964. Successive administrations have on different occasions made attempts to direct government spending towards achieving objectives that have direct bearing on its populace. According to Keynesian view, the increase in public spending on socio-economic and physical structures is important and encourages economic growth. However, Classical economists on the other hand argue that the increase in public expenditure may shift resources from the productive private sector to public sector which they believe is unproductive and hence, crowd out overall performance of the economy. These views indicate that policymakers worldwide including Malawi are under debate whether increase in public spending helps or hinders economic growth. Applying ADF and KPSS tests, Johansen-Juselius co-integration multivariate procedure and TYDL Granger causality test, this study investigates the relationship between government expenditure on roads infrastructure and GDP in Malawi using time series data spanning from 1978 to 2010. ADF and KPSS tests indicate that the series under investigation are integrated of order one (i.e. I(1)). The results of the Johansen co-integration tests indicate a long-run relationship between the roads expenditure and economic growth. The TYDL test indicates the existence of unidirectional causality running from roads expenditure and economic growth which supports Keynes hypothesis that government spending affects economic growth. The study, therefore, concludes that government spending on roads infrastructure causes economic growth, which confirms the main goal of MGDS that aims at achieving economic growth through infrastructure development. Based on these results, the study recommends that government should ensure that both capital and recurrent expenditure are properly managed to accelerate economic growth. More so, Government should promote efficient resource allocation on human capital development by encouraging more private participation to ensure productivity for intensive economic growth.